Information needs of fund managers - Gan, Sock Gee (2009)
This study aims to identify the needs of fund managers and determine the level of satisfaction of the fund managers with the existing sources of information. For the period ended August 1996, the total amount of funds committed was S$2.42 billion (compared with $1.8 billion at the beginning of 1996) under the 16-odd unit trust managers in Singapore. More funds are expected to flow into the hands of these fund management companies as the Central Provident Fund relaxes its investment policy.